2005
DOI: 10.1158/0008-5472.can-05-0985
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Osteosarcoma That Can Predict Response to Chemotherapy

Abstract: Osteosarcoma is the most common malignant bone tumor in children. After initial diagnosis is made with a biopsy, treatment consists of preoperative chemotherapy followed by definitive surgery and postoperative chemotherapy. The degree of tumor necrosis in response to preoperative chemotherapy is a reliable prognostic factor and is used to guide the choice of postoperative chemotherapy. Patients with tumors, which reveal z90% necrosis (good responders), have a much better prognosis than those with <90% necrosis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 47 publications
2
104
0
1
Order By: Relevance
“…12,13 In osteosarcoma, upregulation of TWIST is found to be a predictor in patients with poor response to chemotherapy. 17 Several in vitro studies also agree with these findings. For example, exogenous TWIST expression in mouse embryonic fibroblasts promotes soft agar colony formation, 7 indicating its role in malignant transformation.…”
supporting
confidence: 52%
“…12,13 In osteosarcoma, upregulation of TWIST is found to be a predictor in patients with poor response to chemotherapy. 17 Several in vitro studies also agree with these findings. For example, exogenous TWIST expression in mouse embryonic fibroblasts promotes soft agar colony formation, 7 indicating its role in malignant transformation.…”
supporting
confidence: 52%
“…Simple classifications that were possible for the translocation-associated sarcomas were not possible for osteosarcoma, and these analyses thus far have produced few tangible results. (66,67) Perhaps suggesting whole-genome sequencing may be of value in osteosarcoma is the ability of this approach to identify consistently mutated pathways in genetically complex malignancies such as lung adenocarcinoma. (68) Whether a consistent pattern will emerge from whole-genome sequencing analyses of osteosarcoma awaits completion of these studies.…”
Section: New Resources and Methodsmentioning
confidence: 99%
“…Only few studies comparing gene expression profiles of pretherapeutic biopsies of responsive or nonresponsive patients with an osteosarcoma are available in the literature. [11][12][13] This may be because of the rarity of the tumor and to the difficulty to get frozen specimens from preoperative material. Previous studies have shown that in chemoresistant tumors, genes involved in osteoclastogenesis, extracellular matrix remodeling, bone development, tumor progression, drug resistance and angiogenesis are up-regulated.…”
Section: Uiccmentioning
confidence: 99%
“…Previous studies have shown that in chemoresistant tumors, genes involved in osteoclastogenesis, extracellular matrix remodeling, bone development, tumor progression, drug resistance and angiogenesis are up-regulated. [11][12][13][14][15][16] It is intriguing that there is apparently no overlap between the gene sets identified by the different groups of investigators.…”
Section: Uiccmentioning
confidence: 99%